The Da Vinci codebreaker an easy-to-use fact checker - Garlow, James L. (Minneapolis, Minn. Bethany House, 2006)
"An exposeÃÅ of the bestselling novel. Readers questioning The Da Vinci Code can 'fact check' with this book of terms, events, people and places"--Provided by publisher.
"More than 500 facts & terms"--Cover.
Keywords: Brown, Dan -- 1964- -- Dictionaries; Mary Magdalene -- Saint -- In literature -- Dictionaries; Jesus Christ -- In literature -- Dictionaries; Christianity in literature -- Dictionaries